2023
DOI: 10.1111/1440-1681.13778
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive effects of linzagolix, a novel non‐peptide antagonist of gonadotropin‐releasing hormone receptors, in experimental endometriosis model rats

Abstract: Endometriosis is an oestrogen-dependent disease in which endometrial-like tissue grows outside the uterus in women of reproductive age. Accordingly, control of oestradiol (E2) levels is an effective treatment for endometriosis. Because gonadotropinreleasing hormone (GnRH) is the main controller of E2 secretion, control of GnRH

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…Pharmacokinetic analysis in dogs showed that a dose of 5 mg/kg linzagolix effectively suppressed testosterone levels, with a trough serum linzagolix concentration of ~8 μg/mL, a free form concentration ~8 times higher than its IC 50 value for the dog GnRH receptor. This relationship between linzagolix concentration and IC 50 value was similar to that reported in our previous in vitro study 5 . In normal dogs, the current study found that circulating testosterone concentrations exhibited a circadian rhythm like that reported in humans 14,15 .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Pharmacokinetic analysis in dogs showed that a dose of 5 mg/kg linzagolix effectively suppressed testosterone levels, with a trough serum linzagolix concentration of ~8 μg/mL, a free form concentration ~8 times higher than its IC 50 value for the dog GnRH receptor. This relationship between linzagolix concentration and IC 50 value was similar to that reported in our previous in vitro study 5 . In normal dogs, the current study found that circulating testosterone concentrations exhibited a circadian rhythm like that reported in humans 14,15 .…”
Section: Discussionsupporting
confidence: 91%
“…This relationship between linzagolix concentration and IC 50 value was similar to that reported in our previous in vitro study. 5 In normal dogs, the current study found that circulating testosterone concentrations exhibited a circadian rhythm like that reported in humans. 14,15 Therefore, the dog provided a suitable model animal to examine the clinically relevant effects of linzagolix on testosterone levels.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations